The economic value of childhood socio-emotional skills - Emilia Del Bono; Ben Etheridge; Paul Garcia (University of Essex, Institute for Social and Economic Research (ISER), 2024)
We investigate the relationship between child socio-emotional skills and labour market outcomes using longitudinal data from the 1970 British Cohort Study. We perform a novel factor analysis of child skills and capture four latent dimensions, representing "attention", "conduct", "emotional", and "peers" problems. Conditional on a range of confounding variables, we find that conduct problems, driven by aggression and impulsivity, are associated with positive outcomes in the labour market: higher wages, higher labour supply, sorting into "good" jobs and higher productivity conditional on job tasks. Attention problems are instead negatively associated with labour market outcomes and this relationship is partially accounted for by schooling. We explore different mediating pathways, including through career interests, socialization and mental health - all measured in the adolescent period - but none of these is able to fully explain the association between child skills and later economic outcomes.
Keywords: J24; J62; I21; 330; Socio-emotional Skills; Human Capital; Child Development; Labour Supply; Occupational Sorting